2013
DOI: 10.1002/cmdc.201300340
|View full text |Cite
|
Sign up to set email alerts
|

Probing Binding and Cellular Activity of Pyrrolidinone and Piperidinone Small Molecules Targeting the Urokinase Receptor

Abstract: The urokinase receptor (uPAR) is a cell-surface protein that is part of an intricate web of transient and tight protein interactions that promote cancer cell invasion and metastasis. Here we evaluate the binding and biological activity of a new class of pyrrolidinone (3) and piperidinone (4) compounds, along with derivatives of previously-identified pyrazole (1) and propylamine (2) compounds. Competition assays revealed that the compounds displaced a fluorescently-labeled peptide (AE147-FAM) with inhibition co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Duplicates were removed using ZINC codes, leading to a set of 716113 with unique ZINC codes. A substructure search was carried out on the core structure of pyrazole, piperidinone, and pyrrolidinone compounds that were previously shown to bind to uPAR with inhibition constants ∼ 25 µM (45,50). The fragments that were used for the search are shown in Scheme S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicates were removed using ZINC codes, leading to a set of 716113 with unique ZINC codes. A substructure search was carried out on the core structure of pyrazole, piperidinone, and pyrrolidinone compounds that were previously shown to bind to uPAR with inhibition constants ∼ 25 µM (45,50). The fragments that were used for the search are shown in Scheme S1.…”
Section: Methodsmentioning
confidence: 99%
“…IPR-803 inhibited cancer cell invasion and blocked cancer metastasis in vivo (43). Our work has shown that compounds that bind to uPAR share common structural features and occupy specific pockets in uPAR that accommodate critical hot-spot residues of uPA (45). …”
Section: Introductionmentioning
confidence: 99%
“…23 Interestingly, these compounds were identified in a ligand-based approach using the structure of pyrazole, pyrrolodinone, piperidinone, and butan-amine compounds that were identified by structure-based virtual screening using the structure of uPAR from the uPAR· uPA complex. 21 The carbon that bears the hydroxyl group of the pyrrolinone compounds considered in this work may be prone to attack by nucleophiles. However, the OH group makes a poor leaving group, making covalent adduct formation between the compound and protein unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…18,21,22 Compound 1 was discovered following a substructure search using pyrazole, piperidinone, and pyrrolydi-none compounds as templates. 23 These compounds were shown to bind to uPAR and displace a fluorescently labeled peptide.…”
mentioning
confidence: 99%
“…Pyrazole-based compounds that bind to and inhibit uPAR inhibit the proliferation, invasion, and migration of MDA-MB-231 breast cancer cells via an increase in apoptosis [10]. Similarly, peptides that interfere with the minimal sequence of uPAR required to induce cell motility and angiogenic responses also demonstrated efficacy in vitro in HUVEC and fibrosarcoma cell lines [11].…”
Section: Inhibition Of the Plasminogen Activator System As Cancer Thementioning
confidence: 99%